Preparation method of integrated TiNi alloy with high-strength super-elastic structure and function

Through deep and low-temperature force-induced amorphization technology and ultrafast heat treatment process, the microstructure of TiNi alloys is solved, and the problem of difficulty in achieving high strength and high elasticity at the same time is obtained, and a structural and functional integrated TiNi alloy that is synergistic with high strength and ultraelasticity is obtained.

CN119571230APending Publication Date: 2025-03-07BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411856865.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Traditional TiNi alloys are prone to plastic deformation under low stress conditions and are difficult to achieve high strength and high elasticity at the same time, affecting their long-term service performance.

Method used

The microstructure regulation technology of deep and low temperature force-induced amorphized microstructure is adopted, combined with an optimized ultrafast heat treatment process, to regulate the microstructure of the material to achieve a structural and functional integration of high strength and ultra-elasticity.

Benefits of technology

Through deep low-temperature plastic deformation and ultrafast heat treatment process, a TiNi alloy with both high strength and high elasticity is obtained, which improves the mechanical properties and long-term service performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571230A_ABST
    Figure CN119571230A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an integrated TiNi alloy with a high-strength and super-elastic structure function, and belongs to the field of alloys and preparation methods thereof. The method comprises the following steps: firstly, quantitatively introducing an amorphous phase into a material as a precursor through a novel profound hypothermia force-induced amorphization microstructure regulation and control technology; and then thermodynamic and dynamic behaviors of amorphous crystallization and crystal recrystallization in the variable-form material are regulated and controlled by virtue of ultrafast heat treatment process parameters, and the nano heterogeneous TiNi alloy containing different grain sizes is prepared in a customized manner, so that the problem that high strength and high elasticity in the traditional TiNi alloy are difficult to consider at the same time is solved. The invention provides the preparation method of the integrated TiNi alloy with the high-strength super-elastic structure function. Wide application prospects are realized in the fields of aerospace, biomedical treatment, mechano-electronics, daily life and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of design and preparation of intelligent alloy materials with integrated structure and function, and relates to a method for preparing intelligent metal nano-bulk materials. The material microstructure is regulated by combining amorphization induced by deep low-temperature deformation force with ultrafast heat treatment process path, thereby customizing the design of the structural functional characteristics of the intelligent material. Background Art

[0002] With the continuous development of the times, the requirements for the service performance of smart materials in complex environments are becoming more and more stringent. The development of smart materials with both high strength and high elasticity has become a long-lasting and important research topic. As an important member of the smart material family, TiNi alloy (nickel-titanium alloy) has attracted widespread attention in aerospace, biomedicine, mechanical electronics, and daily life due to its unique superelasticity and shape memory effect. The core property of TiNi alloy lies in its phase transformation behavior, that is, the reversible transformation between the martensite phase and the austenite phase at a specific temperature. Through this phase transformation, TiNi alloy can return to a predetermined shape under certain conditions, or exhibit superelasticity to cope with deformation under greater stress. This feature makes TiNi alloy an important component of various intelligent structures and systems.

[0003] However, although TiNi alloys have shown great potential in the field of smart materials, traditional TiNi shape memory alloys still face some key problems in practical applications. First, TiNi alloys are prone to plastic deformation under low stress conditions, especially under repeated stress, the material will produce dislocation slip, thereby introducing permanent plastic deformation. This deformation will cause the superelasticity and shape memory effect of the material to degrade, affecting its long-term service performance. Secondly, in traditional polycrystalline TiNi alloys, it is difficult to achieve high strength and high elasticity at the same time. High strength usually depends on the integrity of the crystal structure, grain boundary characteristics and dislocation density, while high elasticity is closely related to the phase transformation behavior of the alloy. Because the balance of these properties is difficult to control, traditional polycrystalline TiNi alloys cannot meet the requirements of high strength and high elasticity in complex application environments.

[0004] To solve these problems, researchers have proposed a variety of strategies to improve the performance of TiNi alloys in recent years. Among them, work hardening, aging strengthening, grain refinement and alloying methods have been proven to be effective ways to enhance the functional properties of materials by increasing their critical slip stress. In addition, the optimization of thermomechanical processing technology has improved the phase transformation behavior and mechanical properties of TiNi alloys to a certain extent, and the service performance of the alloy has been optimized by regulating the phase transformation temperature and grain size. At the same time, adjusting the composition ratio of TiNi alloys or introducing other elements can also help improve their phase transformation characteristics and mechanical properties.

[0005] Although these methods have made some progress, the problem of balancing high strength and high elasticity of TiNi alloys has not been fundamentally solved. Generally speaking, increasing the strength of the material will lead to a decrease in superelasticity; conversely, it is difficult to achieve sufficient strength while maintaining superelasticity. This trade-off between strength and elasticity is still the main bottleneck restricting the widespread promotion of TiNi alloys in high-performance applications. Therefore, breaking through this performance contradiction and developing new TiNi alloys with both high strength and superelasticity has become a key issue in the field of TiNi smart materials. Summary of the invention

[0006] In view of the above problems, the purpose of the present invention is to solve the problem that it is difficult to achieve both high strength and high elasticity in traditional TiNi alloys through a new deep low-temperature force-induced amorphization microstructure control technology combined with an optimized ultrafast heat treatment process, and to provide a method for preparing an integrated TiNi alloy with high-strength and super-elastic structure functions.

[0007] The purpose of the present invention is achieved through the following technical methods.

[0008] A method for preparing an integrated TiNi alloy with high strength and superelastic structure function comprises the following steps:

[0009] Step 1: Mix Ti and Ni raw materials according to the alloy atomic percentage, put them into a vacuum induction melting furnace and melt them into alloy mother ingots;

[0010] Step 2: placing the smelted TiNi alloy mother ingot into a vacuum heat treatment furnace for homogenization treatment;

[0011] Step 3: hot rolling the TiNi alloy mother ingot after solid solution into a plate;

[0012] Step 4: After hot rolling, the TiNi alloy mother ingot plate is solution treated and then quenched in water to room temperature;

[0013] Step 5: Use wire cutting to cut the sample into plates, and mill the front and back sides to get the plate sample;

[0014] Step 6: soak the plate sample obtained in step 5 in liquid nitrogen for heat preservation, roll the soaked plate sample, and repeat the soaking and rolling process until the material is deformed by 10-50% by deep low temperature rolling, so as to achieve the deep low temperature plastic deformation force induced amorphization technology to regulate the material microstructure;

[0015] Step seven: ultrasonically clean the surface of the material containing different amorphous phases obtained by deep low-temperature rolling deformation in step six, wrap the sample with carbon paper, and use ultrafast heat treatment equipment to perform electric pulse heat treatment at different temperatures and for different times using pulse discharge mode. The thermodynamics and kinetics of amorphous crystallization and crystal recrystallization inside the deformed material are regulated by ultrafast heat treatment process parameters to obtain an integrated TiNi alloy with high strength and superelastic structure function.

[0016] In the above technical solution, in step 2, the temperature of the homogenization treatment is 800-1000° C., and the time of the homogenization treatment is 4-6 hours.

[0017] In the above technical solution, in step three, the hot rolling temperature is 700-900°C, and the thickness of the plate is 3 mm.

[0018] In the above technical solution, in step 4, the temperature of the solution treatment is 700-900°C, the time of the solution treatment is 0.5-1h, and the room temperature is 18-25°C.

[0019] In the above technical solution, in step five, the thickness of the plate is 2 mm.

[0020] In the above technical solution, in step six, the insulation time is 10-30 minutes, and rolling is carried out on a rolling mill with liquid nitrogen spray on both sides of the roller inlet and outlet. The rolling process follows the principle of multiple passes with small deformation, and the clock rolling method is used for the two different passes before and after.

[0021] In the above technical solution, in step seven, the temperature is 300-600° C. and the time is 1 ms-10 s.

[0022] Beneficial effects of the present invention:

[0023] 1. Compared with the traditional TiNi alloy processing and preparation method, the present invention adopts deep low temperature rolling deformation methods such as liquid nitrogen soaking and spraying to perform deep low temperature deformation on the material from the perspective of maximizing the difficulty of introducing the internal force-induced amorphization mechanism and defect density of the material. Compared with the same deformation at high temperature and room temperature, the deep low temperature plastic deformation is achieved to control the material microstructure and obtain an ultra-high strength alloy.

[0024] 2. The present invention, based on the regulation of the material microstructure by deep low temperature force-induced amorphization technology, simultaneously utilizes ultrafast heat treatment process parameters, and under non-equilibrium heat treatment conditions, regulates the thermodynamics and kinetics of amorphous crystallization and crystal recrystallization inside the deformed material, and customizes the design of bulk nanometal materials containing different grain sizes, thereby obtaining a high-strength, super-elastic, structurally functional integrated TiNi alloy.

[0025] 3. The present invention is applicable to various intelligent TiNi alloy materials, such as TiNi single-phase austenitic alloy, TiNi single-phase martensitic alloy, TiNiX (X=Nb, Co, Fe) alloy and other materials, which can realize the design and preparation of high-strength, super-elastic, structural and functional integrated TiNi alloys.

[0026] 4. This method can effectively improve the mechanical properties of the alloy, extend the service life of the material, and expand the application of TiNi alloy in aerospace, biomedicine and other high-performance intelligent materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Example 1 Step 6 Ti 49 Ni 51 XRD of alloy under different deformation amounts during deep low temperature deformation.

[0028] Figure 2 Example 1 Step 6 Ti 49 Ni 51 DSC of alloy under different deformation amounts during deep low temperature deformation.

[0029] Figure 3 Example 1 Step 6 Ti 49 Ni 51 HV of the alloy at different deformation amounts during deep cryogenic deformation.

[0030] Figure 4 Example 1 Step 7 Ti 49 Ni 51 Typical TEM morphology of the alloy after 50% deep cryogenic deformation and ultrafast heat treatment.

[0031] Figure 5 Example 1 Step 7 Ti 49 Ni 51 Typical high-strength and super-elastic structural function integrated cyclic loading tensile engineering stress-strain curve of the alloy after deep low-temperature deformation combined with ultra-fast heat treatment.

[0032] Figure 6 Example 2 Step 6 Ti 50 Ni 50 XRD of alloy under different deformation amounts during deep low temperature deformation.

[0033] Figure 7 Example 1 Step 6 Ti 50 Ni 50 DSC of alloy under different deformation amounts during deep low temperature deformation.

[0034] Figure 8 Example 1 Step 6 Ti 50 Ni 50 HV of the alloy at different deformation amounts during deep cryogenic deformation.

[0035] Fig. 9 Example 1 Step 7 Ti 50 Ni 50 Typical TEM morphology of the alloy after 50% deep cryogenic deformation and ultrafast heat treatment.

[0036] Fig.10 Example 1 Step 7 Ti 50 Ni 50 Typical high-strength and super-elastic structural function integrated cyclic loading tensile engineering stress-strain curve of the alloy after deep low-temperature deformation combined with ultra-fast heat treatment. DETAILED DESCRIPTION

[0037] The present invention is further illustrated by the following examples, but is not limited to the following examples.

[0038] Embodiment 1:

[0039] The present invention discloses a Ti-type integrated material having high strength and super elastic structure function. 49 Ni 51 The method for preparing the alloy comprises the following steps:

[0040] Step 1: Prepare Ti and Ni raw materials according to Ti 49 Ni 51 The alloy atomic percentage is adjusted and placed in a vacuum induction melting furnace to be melted into an alloy mother ingot;

[0041] Step 2: Melt the Ti 49 Ni 51 The alloy mother ingot is placed in a vacuum heat treatment furnace for homogenization treatment at a temperature range of 800-1000°C for 4-6 hours;

[0042] Step 3: Solvent-dissolved Ti 49 Ni 51 The alloy mother ingot is hot rolled into a plate with a thickness of 3 mm at a temperature range of 700-900°C;

[0043] Step 4: Hot-rolled Ti 49 Ni 51 The alloy mother ingot plate is solution treated at a temperature range of 700-900°C for 0.5-1h and water quenched to room temperature;

[0044] Step 5: Use wire cutting to cut the sample into 2mm thick plates, and mill the front and back sides to make them bright;

[0045] Step six: Soak the plate sample obtained in step five in liquid nitrogen and keep it warm for 10-30 minutes. Rapidly roll the soaked sample on a rolling mill with liquid nitrogen spray on both sides of the roller inlet and outlet according to the principle of multiple passes with small deformation. The two different passes of rolling are performed in a clock rolling manner. The above soaking and rolling process is repeated until the material is deformed by 10-50% at deep low temperature rolling, so as to achieve deep low temperature plastic deformation force-induced amorphization technology to regulate the material microstructure. The changes in XRD, DSC and Vickers hardness under different deformation amounts at deep low temperature are shown as follows: Figure 1 , Figure 2 and Figure 3 As shown. Figure 1 Due to the introduction of lattice defects, crystal refinement and amorphization, Ti 49 Ni 51 The deep cryogenic rolling of the alloy leads to obvious peak broadening in the X-ray diffraction pattern. Figure 2 As the deformation increases, when the deep low temperature deformation exceeds 30%, an endothermic peak is shown at 350℃ during heating, proving that the amorphous phase is successfully introduced. Figure 3 , the microhardness of samples rolled at different deep low temperatures was measured, and the hardness of the cold rolled samples gradually increased with the deformation amount.

[0046] Step 7: Ultrasonic cleaning of the surface of the material containing different amorphous phases after deep low temperature rolling deformation in step 6, wrapping the sample deformed by 50% of deep low temperature rolling with carbon paper, and using ultrafast heat treatment equipment to use pulse discharge mode for electric pulse heat treatment at different temperatures of 300-600℃ and different times of 1ms-10s. The thermodynamics and kinetics of amorphous crystallization and crystal recrystallization inside the deformed material are regulated by ultrafast heat treatment process parameters, thereby obtaining a nano-heterogeneous TiNi alloy with high strength and superelasticity. Ti after deep low temperature rolling deformation of 50% and ultrafast heat treatment 49 Ni 51 The TEM microstructure of the alloy is shown in Figure 4 As shown in the figure, the deep low temperature rolling deformation of 50% successfully introduced the amorphous phase into the material quantitatively, realizing the deep low temperature plastic deformation force-induced amorphization technology to regulate the material microstructure. Subsequently, the bulk nanometal material with different grain sizes was customized through ultra-fast heat treatment. Thus, the high-strength, super-elastic, structural and functional integrated Ti 49 Ni 51 Alloy properties such as Figure 5 shown.

[0047] Embodiment 2:

[0048] The present invention discloses a Ti-type integrated material having high strength and super elastic structure function. 50 Ni 50 The method for preparing the alloy comprises the following steps:

[0049] Step 1: Prepare Ti and Ni raw materials according to Ti 50 Ni 50 The alloy atomic percentage is adjusted and placed in a vacuum induction melting furnace to be melted into an alloy mother ingot;

[0050] Step 2: Melt the Ti 50 Ni 50 The alloy mother ingot is placed in a vacuum heat treatment furnace for homogenization treatment at a temperature range of 800-1000°C for 4-6 hours;

[0051] Step 3: Solvent-dissolved Ti 50 Ni 50 The alloy mother ingot is hot rolled into a plate with a thickness of 3 mm at a temperature range of 700-900°C;

[0052] Step 4: Hot-rolled Ti 50 Ni 50 The alloy mother ingot plate is solution treated at a temperature range of 700-900°C for 0.5-1h and water quenched to room temperature;

[0053] Step 5: Use wire cutting to cut the sample into 2mm thick plates, and mill the front and back sides to make them bright;

[0054] Step six: Soak the plate sample obtained in step five in liquid nitrogen and keep it warm for 10-30 minutes. Rapidly roll the soaked sample on a rolling mill with liquid nitrogen spray on both sides of the roller inlet and outlet according to the principle of multiple passes with small deformation. The two different passes of rolling are performed in a clock rolling manner. The above soaking and rolling process is repeated until the material is deformed by 10-50% at deep low temperature rolling, so as to achieve deep low temperature plastic deformation force-induced amorphization technology to regulate the material microstructure. The changes in XRD, DSC and Vickers hardness under different deformation amounts at deep low temperature are shown as follows: Figure 6 , Figure 7 and Figure 8 As shown. Figure 6 Due to the introduction of lattice defects, crystal refinement and amorphization, Ti 50 Ni 50 The deep cryogenic rolling of the alloy leads to obvious peak broadening in the X-ray diffraction pattern. Figure 7 As the deformation increases, when the deep low temperature deformation exceeds 30%, an endothermic peak is shown at 350℃ during heating, proving that the amorphous phase is successfully introduced. Figure 8 , the microhardness of samples rolled at different deep low temperatures was measured, and the hardness of the cold rolled samples gradually increased with the deformation amount.

[0055] Step 7: Ultrasonic cleaning of the surface of the material containing different amorphous phases after deep low temperature rolling deformation in step 6, wrapping the sample deformed by 50% of deep low temperature rolling with carbon paper, and using ultrafast heat treatment equipment to use pulse discharge mode for electric pulse heat treatment at different temperatures of 300-600℃ and different times of 1ms-10s. The thermodynamics and kinetics of amorphous crystallization and crystal recrystallization inside the deformed material are regulated by ultrafast heat treatment process parameters, thereby obtaining a nano-heterogeneous TiNi alloy with high strength and superelasticity. Ti after deep low temperature rolling deformation of 50% and ultrafast heat treatment 50 Ni 50 The TEM microstructure of the alloy is shown in Fig. 9 As shown in the figure, the deep low temperature rolling deformation of 50% successfully introduced the amorphous phase into the material quantitatively, realizing the deep low temperature plastic deformation force-induced amorphization technology to regulate the material microstructure. Subsequently, the bulk nanometal material with different grain sizes was customized through ultra-fast heat treatment. Thus, the high-strength, super-elastic, structural and functional integrated Ti 50 Ni 50 Alloy properties such as Fig.10 shown.

[0056] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a TiNi alloy with high strength and superelastic structure and function, characterized in that: The steps include: Step 1: Mix Ti and Ni raw materials according to the alloy atomic percentage, put them into a vacuum induction melting furnace and melt them into alloy mother ingots; Step 2: placing the smelted TiNi alloy mother ingot into a vacuum heat treatment furnace for homogenization treatment; Step 3: hot rolling the TiNi alloy mother ingot after solid solution into a plate; Step 4: After hot rolling, the TiNi alloy mother ingot plate is subjected to solution treatment and then quenched in water to room temperature; Step 5: Use wire cutting to cut the sample into plates, and mill the front and back sides to get the plate sample; Step 6: soak the plate sample obtained in step 5 in liquid nitrogen for heat preservation, roll the soaked plate sample, and repeat the soaking and rolling process until the material is deformed by 10-50% by deep low temperature rolling, so as to achieve the deep low temperature plastic deformation force induced amorphization technology to regulate the material microstructure; Step seven: ultrasonically clean the surface of the material containing different amorphous phases obtained by deep low-temperature rolling deformation in step six, wrap the sample with carbon paper, and use ultrafast heat treatment equipment to perform electric pulse heat treatment at different temperatures and for different times using pulse discharge mode. The thermodynamics and kinetics of amorphous crystallization and crystal recrystallization inside the deformed material are regulated by ultrafast heat treatment process parameters to obtain an integrated TiNi alloy with high strength and superelastic structure function.

2. The method for preparing a TiNi alloy having high strength and superelastic structure and function as claimed in claim 1, characterized in that: In step 2, the temperature of the homogenization treatment is 800-1000° C., and the time of the homogenization treatment is 4-6 hours.

3. The method for preparing a TiNi alloy having high strength and superelastic structure and function as claimed in claim 1, characterized in that: In step three, the hot rolling temperature is 700-900°C and the thickness of the plate is 3 mm.

4. The method for preparing a TiNi alloy having both high strength and superelastic structure and function as claimed in claim 1, characterized in that: In step 4, the temperature of the solution treatment is 700-900°C, the time of the solution treatment is 0.5-1h, and the room temperature is 18-25°C.

5. The method for preparing a TiNi alloy having high strength and superelastic structure and function as claimed in claim 1, characterized in that: In step five, the thickness of the plate is 2 mm.

6. The method for preparing a TiNi alloy having high strength and superelastic structure and function as claimed in claim 1, characterized in that: In step six, the insulation time is 10-30 minutes, and the rolling method is to quickly roll on a rolling mill with liquid nitrogen spray on both sides of the roller, following the principle of multiple passes with small deformation, and the clock rolling method is used for the two different passes.

7. The method for preparing a TiNi alloy having both high strength and superelastic structure and function as claimed in claim 1, characterized in that: In step seven, the temperature of the electric pulse heat treatment is 300-600° C., and the time of the electric pulse heat treatment is 1 ms-10 s.